First report on negative association between cyanobacteria and fecal indicator bacteria at San Roque reservoir (Argentina): impact of environmental factors - Halac, Silvana Raquel (2019)
The aim of this study was to evaluate the co-occurrence of some frequent fecal indicator bacteria and cyanobacteria species at San Roque reservoir (SRr), highlighting the relationship between their variability and environmental factors. This study was carried out at SRr (31°22′ S, 64°27′ O) located west of the city of Cordoba, Argentina. Physico-chemical measurements and sampling for microbiological and nutrient determinations were done at three recreational sites, during seasons of major touristic activity (spring-summer), with the aim of identifying temporal patterns of microorganism variability. In addition, we carried out laboratory experiments with local isolated bacteria (Escherichia coli and Enterococcus spp.) and axenic Microcystis aeruginosa cultures to assess an association among these microorganisms and evaluate whether it was positive or negative. Our results showed an inverse relationship between cyanobacteria and thermotolerant coliform bacteria (TtC) at SRr, which was only observed when high cyanobacteria concentration occurred (≥3.4 × 104 to 1.2 × 106 cell.mL−1). Experimental results also showed this type of relationship: E. coli and Enterococcus spp. decreased their growth in the presence of M. aeruginosa. In addition, it was observed that the variability of main phytoplanktonic species and TtC at SRr was mainly explained by temporal patterns, that is, the seasonal changes and the hydrological year. In summary, our data indicated that cyanobacteria high abundance during bloom periods could be an inhibiting factor for bacteria growth at SRr. Moreover, we demonstrated that nutrients such us P and N are not the main factors determining the variability of studied microorganisms in this eutrophic reservoir, but other factors, such as climatic conditions (temperature and precipitations), have a major influence. This study would provide a more comprehensive view on the dynamics of microorganism populations with sanitary relevance in eutrophic reservoirs.